Women’s Religious Authority and the Governance of Muslim Philanthropy: The Càntakun Succession Conflict in Senegal - Alassane Sow; Muhmmad Lisman; Muhammad Syahrullah (MD Research Center Yogyakarta, 2026)
Islamic Succession conflicts within Sufi brotherhoods in Senegal often expose tensions between competing forms of religious legitimacy, yet their implications for philanthropic governance and women’s participation remain underexplored. This study examines the Caliphate succession conflict within the Càntakun community following the death of Sheikh Béthio Thioune, focusing on how competing legitimacy claims reshape religious authority, philanthropic governance, and gender relations. Employing a qualitative case study design, the research draws on twenty semi-structured interviews, five focus group discussions, and eight participant observations conducted across nine localities in Senegal. The findings reveal that the succession dispute is not merely a theological contest but a struggle over control of philanthropic resources, including adiya, donations, land, and diaspora networks. Sokhna Aida Diallo’s claim to caliphal authority challenges patriarchal norms and expands women’s participation in Muslim philanthropy, while Saliou Thioune’s claim reinforces hereditary succession and institutional orthodoxy. The study argues that routinization of charismatic authority is a contested process shaped by gender dynamics, with significant implications for community participation and institutional continuity. These findings contribute to broader discussions on gender, religious authority, and philanthropic governance in Muslim societies.